Comments on Westera et al. (2022), 'Support for people with dementia experiencing severe responsive behaviours: Unpacking the disconnect between policy and practice'. - Andreotta, Matthew; Atee, Mustafa; Morris, Thomas; Alford, Marie (2022)
LETTER TO THE EDITOR